ANALYSIS OF BORDER SERVICE IMAGE FORMATION PROVISION - Бобровський, Т.А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article deals with the analysis of the border agencies image formation, its functions, structure and tools to determine the formation of modern effective methodological tools that has the most effective impact on changing the image of state structure within the governance. The conclusion about the need for extensive use of Internet resources and development of human resource management in the communication and management approaches to improve the image of border agency was made.